Morphological features of thyroid gland of children who have died aged till 6 months from a HIV-infected of mothers. - Sherstiuk, S. A.; Sorokina, I. V. (Морфологія / Morphologia / Morfologìâ, 2011)
In a thyroid gland of children who have died aged till 6 months, from a HIV-infected of mothers thanks to morphological and morphometric researches it is taped reduction of internal diameter of follicles, heights follicular cells, and as increase the stromal and reduction colloid components, testifying about change secretion type, apparently, caused by influence antenatal and a postnatal hypoxia.